MENGEMBANGKAN MEDIA PEMBELAJARAN BERBASIS HIGHER ORDER THINKING SKILLS (HOTS) UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMK - Sumandya, I Wayan; Mayudana, Kadek Yogi; Wiadnyana, I Gusti Agung Gede (LPPM IKIP PGRI Bali, 2019)
Higher Order Thinking Skills (HOTS) is a warm conversation in the world of education. Learning media that are able to develop Higher Order Thinking Skills (HOTS) are inadequate. This study aims to develop learning media based on Higher Order Thinking Skills (HOTS) to improve the mathematical communication skills of vocational students. This research is part of a larger study using development research as the method. The subjects of the study were 10th grade students of Wira Harapan Vocational School consisting of 36 students (19 male and 17 female) 2018/2019 academic year and mathematics subject teachers at Wira Harapan Vocational School. Data collected from questionnaires and observations during learning. Data were analyzed using content analysis techniques and code based on the type of student and teacher responses. The results show that (a) the total student responses to the implementation of the HOTS-based learning media were 126 consisting of 80.56% positive responses and 19.44% negative responses. (b)) the total teacher response to the implementation of HOTS-based learning media is 37 which consists of 80% positive and 20% negative responses. Based on the results of data analysis of student and teacher responses to the implementation of instructional media, it can be concluded that students are helped to understand problems based on HOTS, are active in learning and students are able to prepare themselves to be ready and confident when facing HOTS question-based examinations.